La Renaixença al País Valencià - Vicent Simbor Roig (Caplletra: Revista Internacional de Filologia, 2015)
The autor covers the development of the Renaixença in Valencia (1830-1909), and divides it into two periods, the beginning (1830-1859) and splendor (1859-1909). This latter stage is further sub-divided into the period between 1859 and 1874, which was dominated by Llorente and his conservative group, and that between 1874 and 1909, which was characterized by the incorporation into the movement of Constantí Llombart and his progressive group.